Business is Unusual: Discussing the Philosophy of Astra Code of Ethics - ., Subagyo; Manajemen, I (KnE Social Sciences, 2018)
Purpose – This study aims to explore the foundation and philosophy of Astra in building Astra Code of Conduct. Design/methodology/approach – The review is run by conducting theoretical review through references related to ethics and code of ethics as well as reviewing the Astra Code of Ethics published through the Astra website (www.astra.co.id). In addition, some other materials relevant to this study is also used, among others: Annual Report, Sustainable Report, and books under the title ”Astra: on Becoming Pride of the Nation”. The result of the theory and data/information obtained is synthesized by using content analysis approach. Finding– Astra has the foundation and philosophical basis that comes from the personality and character of William Suryadjaya, Astra’s founder. Astra adheres to the thought that business is unusual. Practical implication– The results of this study can be used as a theoretical framework for conducting further studies or research related to Astra Corporate Ethics. Originality/value– This review provides value for the development of Humanism Management. Keywords: Astra, Philosophy, Catur Dharma, Sustainability, Good Corporate Citizen